Pemahaman Mahasiswa Terhadap Makna Halal Toyyib Dalam Al-Qur’an (Analisis Fenomenologi Pola Makan Mahasiswa Progam Studi Ilmu Al-Qur’an Dan Tafsir UIN RMS Surakarta 2023 di Tempat Kos) - Nasywa Lulu Azzahra Sutopo; Muhammad Habib Zainul Huda (Inspirasi Dunia: Jurnal Riset Pendidikan dan Bahasa, 2025)
The phenomenon of IAT students who live in boarding houses and often consume fast food encourages the author to conduct this research. The reason is, so that what IAT students understand in lectures towards the meaning of Halal and Tayyib is implemented in everyday life, especially in boarding houses. This research is Descriptive Qualitative research. Data obtained through interviews via Whatshap chat. The research subjects amounted to 9 students consisting of 3 students in each class (A, B, and C). The theory that researchers use is Edmund Husserl's Phenomenology Theory. This theory prioritizes social phenomena to bring up a shared awareness of something. The results of this study indicate that: (1). The understanding of IAT Batch 2023 students towards the meaning of Halal and Tayyib as in the Qur'an is very good. (2) There are various phenomena revealed related to fast food eating patterns of IAT 2023 boarding school students. (3) Fast food or food that is Halal and Tayyib is very influential on student concentration, both short and long term.